2018
DOI: 10.1002/hipo.22954
|View full text |Cite
|
Sign up to set email alerts
|

On the (a)symmetry between the perception of time and space in large‐scale environments

Abstract: Cross-dimensional interference between spatial and temporal processing is well documented in humans, but the direction of these interactions remains unclear. The theory of metaphoric structuring states that space is the dominant concept influencing time perception, whereas time has little effect upon the perception of space. In contrast, theories proposing a common neuronal mechanism representing magnitudes argue for a symmetric interaction between space and time perception. Here, we investigated space-time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
(92 reference statements)
3
14
0
Order By: Relevance
“…Although there have been some timing studies implementing more naturalistic paradigms and stimuli ( Boltz, 2005 ; Brunec et al, 2017 ; Riemer et al, 2018 ; Roseboom et al, 2019 ; Schlichting et al, 2018 ; Tobin et al, 2010 ; van Rijn, 2014 ), the number of studies directly comparing the effects of naturalistic versus more abstract paradigm versions is rather scarce ( Maaß et al, 2021 ; Thanopoulos et al, 2018 ). For example, investigating the phenomenon of intentional binding ( Haggard et al, 2002 ), Thanopoulos et al (2018) found that the tendency to underestimate the temporal interval between a self-initiated action and a subsequent visual stimulus is more pronounced when the nature of the visual stimulus is a meaningful part in a plausible sequence of events (e.g., an image of a hand about to slap a table surface, followed by an image of the same hand touching the surface).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been some timing studies implementing more naturalistic paradigms and stimuli ( Boltz, 2005 ; Brunec et al, 2017 ; Riemer et al, 2018 ; Roseboom et al, 2019 ; Schlichting et al, 2018 ; Tobin et al, 2010 ; van Rijn, 2014 ), the number of studies directly comparing the effects of naturalistic versus more abstract paradigm versions is rather scarce ( Maaß et al, 2021 ; Thanopoulos et al, 2018 ). For example, investigating the phenomenon of intentional binding ( Haggard et al, 2002 ), Thanopoulos et al (2018) found that the tendency to underestimate the temporal interval between a self-initiated action and a subsequent visual stimulus is more pronounced when the nature of the visual stimulus is a meaningful part in a plausible sequence of events (e.g., an image of a hand about to slap a table surface, followed by an image of the same hand touching the surface).…”
Section: Discussionmentioning
confidence: 99%
“…The most minimal way to test for a potential effect of irrelevant contextual information consists in the implementation of a naturalistic scene in which the stimuli are embedded. The use of more realistic stimuli has been proposed earlier (Riemer et al, 2018;Roseboom et al, 2019;Schlichting et al, 2018;van Rijn, 2014), and a recent study suggested that the temporal context effect-an effect that is associated with memory impairments (Maaß et al, 2019)-is more pronounced when probed with naturalistic compared with abstract stimuli (Maaß et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supporting this hypothesis comes from multiple behavioural studies examining the interference effect between the perception of space and time. Their findings suggest that humans are unable to ignore irrelevant spatial information when estimating time ( Brunec et al, 2017 ; Brunec et al, 2020 ; Casasanto et al, 2010 ; Casasanto & Boroditsky, 2008 ) and cannot ignore irrelevant temporal information when estimating space ( Cai & Connell, 2015 ; Cai & Wang, 2021 ; Riemer et al, 2018 ). In addition to behavioural findings, multiple neuroimaging studies have suggested that a common neural mechanism is responsible for spatial and temporal processing.…”
mentioning
confidence: 99%
“…However, the extent to which the abovementioned domains overlap, as well as their specific mechanisms, remains to be clarified. For example, it has been shown that the interference effect between spatial and temporal perceptions is often asymmetric; in many cases, the perception of time is influenced by spatial information, while the perception of space is less or not affected by temporal information ( Casasanto et al, 2010 ; Casasanto & Boroditsky, 2008 ; Riemer et al, 2018 ). These findings suggest that, while these two dimensions are indeed related to each other, their processing mechanisms are to some extent separable.…”
mentioning
confidence: 99%
See 1 more Smart Citation